Error Analysis In Master’s Theses By Non-Arabic Speakers In International Islamic University Malaysia/ تحليل الأخطاء في رسائل الماجستير لدارسي العربية الناطقين بغيرها في الجامعة الإسلامية العالمية بماليزيا - Hamawiya, Adham; Wan Ahmad, Wan Rusli; Altabaa, Homam; H. Osman, Rahmah Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
One of the key characteristics of academic writing is its precision in expressing facts and ideas and its avoidance of subjective impressions, rhetorical styles, and ambiguous formulations. When students write their theses in foreign languages, proficiency in a foreign language is essential for high-quality academic writing. Numerous errors may be found in the theses without such proficiency, undermining the students’ efforts. This study adopted a descriptive-analytical approach to quantitatively and qualitatively analyse the writing errors found in six master's theses completed by International Islamic University Malaysia students. Among the study’s key findings is that language is the most suitable domain for applying the criterion of right and wrong. Writing errors stem from two primary sources: internal within the language and external from other languages. Moreover, these errors may intersect or overlap.